Children Marriage Phenomenon During The Covid-19 Pandemic - Gussevi, Sofia; Marlia Indriyani, Shofa; Supiana, Pebi (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
This research departs from the phenomenon of child marriage which occurs a lot in society. Even during the current Covid-19 pandemic, the number is increasing. This can be seen from the number of Marriage Dispensation cases submitted to the Purwakarta Religious Court. In 2019, the Marriage Dispensation was recorded as many as 92 cases. In 2020, during the Covid-19 pandemic, the number of Marriage Dispensations increased to 258 cases. On the other hand, during the Covid-19 pandemic, there was an increasing number of divorce cases, especially divorce cases for economic reasons submitted to the Religious Courts. This study aims to explain the factors causing child marriage during the Covid-19 pandemic and the factors causing the increase in the number of Marriage Dispensation cases during the Covid-19 pandemic at the Purwakarta Religious Court and the strategy of the Purwakarta Religious Court in dealing with the increasing number of Marriage Dispensation cases during the pandemic. Covid-19. The methodology used in this research is descriptive qualitative. Based on the study results, it can be concluded that the factors that cause child marriage are economy, education, parents, socio-culture and pregnancy before marriage. The factors causing the increase in the number of Marriage Dispensation cases during the Covid-19 pandemic at the Purwakarta Religious Court were the socio-cultural conditions of the community in 2020 who experienced the Covid-19 pandemic and the increasing legal awareness of the community. The strategy of the Purwakarta Religious Court in dealing with the increasing number of Marriage Dispensation cases during the Covid-19 pandemic is that the consideration in granting the Marriage Dispensation is not only in terms of economic problems, namely the prospective husband already has a job and a steady income, but also considers and gives views to the applicant regarding what to do after marriage